Role of Financial Sector Development in the Nexus Between Inclusive Growth and Poverty: A Regional Comparative Analysis from Sub-Saharan Africa - Abiodun S. Olayiwola; Temidayo O. Akinbobola (Research in Applied Economics, 2024)
The problem of poverty in the developing countries and what makes Sub-Saharan Africa (SSA) a region with the “highest number of poor people” in the world remains a topical issue that requires serious research attention. Following extant studies, in which the mediating role of financial sector development has not been taken into consideration in their finance- growth and poverty nexus, this study deviates by using two measures of poverty level: absolute and multidimensional poverty level; and at the same time provides comparative analyses at SSA sub-regional communities. Our findings reveal that the effects of inclusive growth on poverty reduction (both absolute and multidimensional level), for most sub-regions in SSA except Central African countries, are positive. While the mediating role of financial sector development appeared to be slightly different with mixed results. In West and Central African countries, the mediating role of the financial sector, though very weak, complements the inclusive growth effects on poverty reduction. On the contrary, financial sector development does not complement inclusive growth when it comes to poverty reduction in South African countries. Also, financial sector development does not complement the absolute poverty reduction effect of inclusive growth in the East African sub-region but the result is otherwise under multidimensional poverty reduction. Therefore, we recommend that financial sector development in most SSA countries should be improved upon through relevant monetary policy that promotes financial innovations, financial sector reforms, efficiency in financial inclusion across the region, and at the same time efforts should be geared toward directing some of the gains in financial sector development to inclusive growth-enhancing activities in southern African sub-region.